Financial reorganization as a means of saving troubled commercial projects from bankruptcy: An analytical study in the UAE Bankruptcy Law No. 51 of 2023 - Mohammad Saad Ali Al Armman (Universitas Ahmad Dahlan, 2026)
Introduction to the Problem: Avoiding commercial projects falling into the abyss of bankruptcy is a modern philosophy upon which modern legislation is based, based on its awareness of the importance of the role that commercial projects in general play in the economic development of countries, which requires attention from those in charge of them. Purpose/Study Objectives: This study came to clarify the position of the Emirati legislator on this method and its role in reducing the declaration of bankruptcy of a faltering commercial project by evaluating the financial situation of the debtor, as the Emirati legislator approved in the Bankruptcy Law the establishment established a unit in the Ministry of Justice called the Financial Reorganization Unit and assigned to it a group of Specializations Design/Methodology/Approach: The financial reorganization method is one of the alternative methods developed by the UAE legislator to avoid bankruptcy for companies, by conducting an analysis of the status of the faltering commercial project, finding out the reasons for its faltering, and re-evaluating it. This certainly requires that these projects have a strong desire to address their financial situation before it worsens. Hence, the UAE bankruptcy law is more concerned with saving the commercial project to overcome its financial difficulties than defaming the debtor who owns the project, by introducing a financial reorganization mechanism to protect the commercial project and avoid its bankruptcy. Findings The study concluded that establishing this unit in the Ministry of Justice and granting it a group of specializations gave it an administrative character, not a judicial one. Granting the right to choose financial reorganization experts’ conflicts with the jurisdiction of the competent court to make such a choice. Paper Type: Research Article